Business Intelligence (BI) system evolution: a case in a healthcare institution. (10th June 2016) - Safwan, Ehsanur Rahman; Meredith, Rob; Burstein, Frada
Abstract: Business Intelligence (BI) systems are an important part of many organisations' IT portfolios. While the evolutionary nature of other kinds of decision support technology has been noted, there is little research investigating the evolutionary nature of BI systems. This paper presents a case study of a BI system development in a large Australian healthcare institution and uses evolutionary theories from decision support systems (DSS) to understand the system evolution observed. The paper concludes that the theories describing evolution in DSS can also be effectively applied to BI as well. BI practitioners and developers should be aware of evolutionary triggers, as well as the different kinds of evolution that can affect BI system evolution.